2017
DOI: 10.1016/j.tvjl.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying center of pressure variability in chondrodystrophoid dogs

Abstract: The center of pressure (COP) position reflects a combination of proprioceptive, motor and mechanical function. As such, it can be used to quantify and characterize neurologic dysfunction. The aim of this study was to describe and quantify the movement of COP and its variability in healthy chondrodystrophoid dogs while walking to provide a baseline for comparison to dogs with spinal cord injury due to acute intervertebral disc herniations. Fifteen healthy adult chondrodystrophoid dogs were walked on an instrume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The COP is the two-dimensional projection of the center of gravity and reflects the orientation and movements of the body. It changes constantly, creating a COP or sway path [18][19][20]. The COP displacement can be determined by means of pressure sensitive walkway systems (PSW) or force-plates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COP is the two-dimensional projection of the center of gravity and reflects the orientation and movements of the body. It changes constantly, creating a COP or sway path [18][19][20]. The COP displacement can be determined by means of pressure sensitive walkway systems (PSW) or force-plates.…”
Section: Introductionmentioning
confidence: 99%
“…The COP displacement can be determined by means of pressure sensitive walkway systems (PSW) or force-plates. While force-plates are the gold-standard device for these measurements, PSW are lightweight, and easily transportable, making them more suitable for clinical settings [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…By tracking a marker positioned in the interscapular area with infrared sensors, the movement of the body COP relative to this anatomical marker could be recorded. It was found that the COP was moving in a butterfly-like path during the gait cycle [22]. Another study with a similar design examined non-ambulatory dogs with thoracolumbar spinal cord injury.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the COP provides a dynamic reflection of global locomotion and postural control [28], and it has been used to quantify various gait abnormalities [29]. In dogs, COP has been investigated in healthy animals [30], in animals with orthopedic [31,32] and neurological conditions [29], and to test the efficacy of a treatment [33]. The COP may be a useful tool to obtain information regarding biomechanical modifications and postural control during exercises in healthy and impaired animal.…”
Section: Introductionmentioning
confidence: 99%